Higher Grade Glioma Increases the Risk of Postoperative Delirium: Deficient Brain Compensation Might Be a Potential Mechanism of Postoperative Delirium - Huang, Hua-Wei; Zhang, Xiao-Kang; Li, Hao-Yi; Wang, Yong-Gang; Jing, Bin; Chen, You; Patel, Mayur B.; Ely, E. Wesley; Liu, Ya-Ou; Zhou, Jian-Xin; Lin, Song; Zhang, Guo-Bin (Frontiers in Aging Neuroscience, 2022)
Objective: The brain compensation mechanism in postoperative delirium (POD) has not been reported. We uncovered the mechanism by exploring the association between POD and glioma grades, and the relationship between preoperative brain structural and functional compensation with POD in frontal glioma patients. Methods: 335 adult glioma patients were included. The multivariable analysis was examined the association between tumor grade and POD. Then 20 patients with left frontal lobe glioma who had presurgical structural and functional magnetic resonance imaging (MRI) data and Montreal Cognitive Assessment (MoCA) in this cohort were analyzed. We measured gray matter volume (GMV) and functional connectivity (FC) in patients with (n=8) and without (n=12) POD and healthy controls (HCs) to detect the correlation between the structural and functional alteration and POD. Results: The incidence of POD was 37.3 %. Multivariable regression revealed that high-grade glioma had approximately six times the odds of POD. Neuroimaging data showed that compared with HC, the patients with left frontal lobe glioma showed significantly increased GMV of right dorsal lateral prefrontal cortex (DLPFC) in non-POD group and decreased GMV of right DLPFC in POD group, and POD group exhibited significantly decreased FC of right DLPFC, and the non-POD group showed the increasing tendency. Partial correlation analysis showed that GMV in contralesional DLPFC were positively correlated with preoperative neurocognition, and the GMV and FC in contralesional DLPFC were negatively correlated with POD. Conclusions: Our findinds suggested that insufficient compensation for injured brain region involving cognition might be more vulnerable to suffering from POD.